1982
DOI: 10.1063/1.863681
|View full text |Cite
|
Sign up to set email alerts
|

An energy loss coefficient in fluid buckling

Abstract: A jet of viscous fluid falling against a flat plate may become unstable and buckle. The buckling process is postulated as a discontinuity, and a simple model is developed that indicates a loss of energy in the fluid buckling. Experimental values of the energy loss coefficient are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The bouncing [137] of a jet raises similar questions about fluid elasticity and surface tension as well as about the mathematical nature of the flow as a boundary-value problem and the particular issue of the influence of down-stream boundary conditions on the flow of the jet as a whole. A quantitative investigation of the coiling (or buckling) of the fluid jet is presented by Cruickshank [138] who refers to earlier work by G.I. Taylor.…”
Section: Discussionmentioning
confidence: 99%
“…The bouncing [137] of a jet raises similar questions about fluid elasticity and surface tension as well as about the mathematical nature of the flow as a boundary-value problem and the particular issue of the influence of down-stream boundary conditions on the flow of the jet as a whole. A quantitative investigation of the coiling (or buckling) of the fluid jet is presented by Cruickshank [138] who refers to earlier work by G.I. Taylor.…”
Section: Discussionmentioning
confidence: 99%
“…Physically, the buckling of a viscous plume can be attributed to the fact that the stress changes from tension to compression as the fluid approaches the surface, and in the region of compression its behaviour does indeed have some superficial characteristics in common with that of an elastic column. Following Taylor's paper there was little quantitative work on this problem until Cruickshank & Munson (1981, 1982a) made a thorough study of both axisymmetric and plane jets. They presented experimental results for jets of viscous silicone oil pumped through a circular orifice or a slit and impinging on a flat plate held a known distance H below the orifice.…”
Section: Methodsmentioning
confidence: 99%
“…He recognized that a longitudinal compressive stress is a primary factor of the folding instability. A quasi one-dimensional analysis was developed for buckling of an axisymmetric (Tchavdarov et al 1993;Yarin 1993;Entov and Yarin 1984;Cruickshank andMunson 1983, 1982b) and thin plane jets (Yarin and Tchavdarov 1996) and for both cases (Cruickshank 1988;Cruickshank and Munson 1982a). Cruickshank and Munson (1982a) reported that the compressive stress associated with fluid buckling was related with energy loss which was experimentally determined for the axisymmetric and the plane jets.…”
Section: Introductionmentioning
confidence: 98%
“…A quasi one-dimensional analysis was developed for buckling of an axisymmetric (Tchavdarov et al 1993;Yarin 1993;Entov and Yarin 1984;Cruickshank andMunson 1983, 1982b) and thin plane jets (Yarin and Tchavdarov 1996) and for both cases (Cruickshank 1988;Cruickshank and Munson 1982a). Cruickshank and Munson (1982a) reported that the compressive stress associated with fluid buckling was related with energy loss which was experimentally determined for the axisymmetric and the plane jets. According to the perturbation analysis (Cruickshank 1988), the slenderness ratio of the viscous thread was found to determine the onset of buckling, where the slenderness can be defined as the ratio of the thickness and height of the thread.…”
Section: Introductionmentioning
confidence: 98%